Implementasi Peraturan Daerah Kabupaten Klungkung Nomor 2 Tahun 2018 tentang Retribusi Pelayanan Pasar - Gede Dwiki Cahyadi; Anak Agung Sagung Laksmi Dewi; I Wayan Arthanaya (Warmadewa Press, 2022)
The traders who sell in the Public Market owned by the Klungkung Regency Government have an obligation to pay a market levy. The Regional Government together with the Klungkung Regency Cooperatives and UMKM Service are institutions in charge of retribution in accordance with statutory regulations. The purpose of this study is to discuss the implementation of the Klungkung Regency Regional Regulation No. 2 of 2018 on Levy Taxes and to examine the legal consequences of the Klungkung Regency Regional Regulation No. 2 of 2018 concerning Market Service Fees, Especially in the Semarapura Market. This study uses an empirical method using a sociological approach, a conceptual approach, and a factual approach. Market levies have an influence on local revenue (PAD) as a significant source of revenue for routine and development financing in an autonomous region. The continuation of the Covid-19 pandemic, namely realizing the abolition of fines if the market retribution arrears are more than two months and only required to pay the principal, referring to the policies issued by the cooperative and MSME services as government institutions that take shelter in managing user charges. Public markets in Klungkung Regency that are required to pay a levy are Semarapura Public Market, Galiran Public Market, Kusumba Public Market, Mentigi Public Market, and Senggol Public Market.